Iatrogenic retractile quadriceps fibrosis within children in Benin: Epidemiological, clinical, therapeutical aspects - A S Gbenou; G T Kpadonou; A M Fiogbe; E Zoumenou; M J Alao (Wolters Kluwer Medknow Publications, 2013)
Background: In tropical countries, iatrogenic retractile quadriceps fibrosis (IRQF), the cause of walking handicap in children, is often the result of intraquadricipital injection of quinine salts. The aim of this review was to analyse the epidemiological, clinical, therapeutic aspects and outcome of IRQF in children admitted in three hospitals in Benin Republic. Patients and Methods: It was a 10-year retrospective, descriptive and analytic survey of IRQF, involving 81 children aged from 8 months to 15 years. Iterative mobilization of the knee (IMK) or modified distal quadriceps plasty by Thompson-Payr's technique (MDQTPT), with a POP on the knee in flexion position, was performed with additional functional rehabilitation. The results were evaluated on knee flexion gain and walking quality. Data were processed using Epi Info 3.2 software. Results: Patients' average age was 7.60 years. Children of 6-10 years were most affected; sex ratio was 1.02. Lesions were unilateral (71.6%) and bilateral (28.4%). The knees' stiffness was in flexion (10.57%), rectitude (64.42%) and recurvatum (25%). The amyotrophy of the thigh was found in 79.42 %. The IMK was successful in eight cases (7.69 %) and the MDQTPT was done in 98 cases (94.23%) associated with femoral osteotomy in 13 cases (12.50%). In post-surgical period, skin necrosis and fractures occurred respectively in 15.31% and 5.10%. Results were good in 92.31% of cases. Conclusions: IRQF in children do exist in our settings. The treatment that is based on MDQTPT associated to rehabilitation leads to acceptable outcome.